Catalytic enantioselective construction of vicinal quaternary carbon stereocenters. Issue 35 (17th August 2020) - Zhou, Feng; Zhu, Lei; Pan, Bo-Wen; Shi, Yang; Liu, Yun-Lin; Zhou, Jian
Abstract : This review summarizes the advances in catalytic enantioselective construction of vicinal quaternary carbon stereocenters, introduces major synthetic strategies and discusses their advantages and limitations, and outlines the synthetic opportunities. Abstract : This review summarizes the advances in the catalytic enantioselective construction of vicinal quaternary carbon stereocenters, introduces major synthetic strategies and discusses their advantages and limitations, highlights the application of known protocols in the total synthesis of natural products, and outlines the synthetic opportunities.